2022
DOI: 10.1038/s41417-022-00497-8
|View full text |Cite
|
Sign up to set email alerts
|

Combination regimen of granulocyte colony-stimulating factor and recombinant human thrombopoietin improves the curative effect on elderly patients with leukemia through inducing pyroptosis and ferroptosis of leukemia cells

Abstract: Leukemia ranks as the one of most common causes of death from tumor. 51.4% of patients with leukemia are over 65 years old. However, the median overall survival (OS) of elderly leukemia patients is less than one year. It is urgent to explore more effective treatments for elderly patients with leukemia. Our recent prospective phase II single-arm study has revealed that combination regimen of granulocyte colony-stimulating factor (G-CSF) and recombinant human thrombopoietin (rhTPO) could improve the curative eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…The recombinant human thrombopoietin induces ferroptosis in leukemia cells by EP300. 33 NSCLC cell ferroptosis was decelerated, evidenced by downregulated levels of iron, ACSL4, ROS, and MDA and upregulated levels of GPX4, SOD, and GSH, after upregulating EP300.…”
Section: Discussionmentioning
confidence: 99%
“…The recombinant human thrombopoietin induces ferroptosis in leukemia cells by EP300. 33 NSCLC cell ferroptosis was decelerated, evidenced by downregulated levels of iron, ACSL4, ROS, and MDA and upregulated levels of GPX4, SOD, and GSH, after upregulating EP300.…”
Section: Discussionmentioning
confidence: 99%
“…Then 10 µL CCK-8 solution (#C0037, Beyotime Biotechnology, Shanghai, China) at a 1/10 dilution was added in each well to incubate MM cells for 2 h at 37 °C, and absorbance at 450 nm was assayed by Multiscan MK3 (Thermo Fisher Scientific, Waltham, MA, USA) to identify cell viability or proliferation rate. Cell proliferation was measured after 1–3 days, while cell viability was determined in 24 h after PI treatment, as previously described [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…In a phase 2 trial, Xiaoyu Liu and his team explored the potential anti-leukemia effects of a combination therapy involving granulocyte-colony stimulating factor (G-CSF), thrombopoietin (TPO), and low-dose chemotherapy in elderly patients with acute myeloid leukemia (AML) [ 215 ]. Their findings revealed that TPO triggers ferroptosis by inhibiting EP300-mediated GPX4 transcription, while G-CSF induces pyroptosis via neutrophil elastase, which in turn activates Gasdermin D (GSDMD) in AML cells [ 216 ].…”
Section: Promoting Ferroptosis As a Novel Leukemia Treatment Strategymentioning
confidence: 99%